Apparent mass during silo discharge Nonlinear effects related to filling protocols - Peralta, Juan Pablo (2017)
We study the evolution of the force exerted by a granular column on the bottom surface of a silo during its discharge. Previous to the discharge, we prepare the system using different filling procedures: distributed, i.e. a homogeneous rain of grains across the cross-section of the silo; concentric, a granular jet along the silo axis; and a combination of both, i.e. filling half of the silo using one procedure and the second half using the other. We observe that each filling protocol leads to distinctive evolutions of the apparent mass (i.e., the effective weight sensed at the base) during the discharge. Interestingly, the use of combined filling protocols may lead to a reduced apparent mass, smaller than any other achieved with a simple filling. We propose a model based on the Janssen rationale that quantitatively accounts for the latter puzzling experimental observation.